Catastrophic Consequences of Spain's Language Policy against the Background of Russia's Language Policy - Rafael Guzman Tirado (National Research Mordova State University, 2023)
Introduction. The problem of preserving and protecting the native language today is one of the main ones facing any people thinking about their future in the conditions of globalization, European economic integration and a modern multinational and multi-confessional state. The purpose of this article is to examine the internal processes of the destruction of the status of a single official language as a link between the country and the analysis of the discriminatory status of the Spanish language in modern Spain and the prediction of the consequences of such discrimination of language policy, as well as a comparative analysis of the language situation in Spain and Russia. Materials and Methods. This section specifies what has served as material for the analysis and describes the research techniques used. The object of the study is the Spanish language as the official language of the Kingdom of Spain, its role and its changes in the regions in the process of political processes over the past decades. Comparative- historical and typological research methods are used, as well as methods of observation, analysis, modeling. Results. This is the main section, which aims to confirm or reject a working hypothesis (or hypotheses) by means of analysis, synthesis and elucidation of data. The reasons for the unbalanced state of the language situation in Spain, as well as the negative consequences of the language policy pursued by the government, are analyzed. Practical recommendations have been developed to overcome the existing critical problems in the field of the country's language policy, based on the Russian example. Discussion and Conclusion. In this part, the results are to be briefly summarized and the main directions for further research indicated. The results presented in the article contribute to the scientific understanding of the problem of the status of the state official language in modern Spain. They contribute to the development of awareness of the seriousness and danger of the problem. If we Spaniards do not realize the seriousness of what is happening and do not force the government, the opposition and all legitimate parties to respond to this critical situation, then the future of the Spanish language and the Spaniards themselves in Spain seems pessimistic, since we will be foreigners in our beautiful country.